The Relationship Between Islah Al-Afrad and Social Welfare: Concepts and Relevance in the Contemporary Era - Thoyyibatus Sa’idah; Ahmad Syukron (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This paper aims to examine the relationship between the concept of Islah al-Afrad (individual reform) and social welfare from an Islamic perspective, as well as to explore its relevance in the contemporary era. This study is motivated by various modern social problems that indicate that structural development alone has not been fully capable of realizing societal well-being without being accompanied by individual moral and spiritual transformation. Therefore, Islah al-Afrad is viewed as a crucial foundation for building a harmonious and just social order. This research employs a qualitative approach based on a literature review, utilizing descriptive-analytical analysis of normative Islamic sources, such as the Qur’an and hadith, as well as relevant contemporary literature. The findings indicate that Islah al-Afrad is closely linked to the creation of social welfare, as individuals of good character and integrity will contribute to the formation of a just, caring, and civilized society. This concept emphasizes that sustainable social change must begin with the internal transformation of the individual, which then impacts the improvement of broader social structures. In the contemporary context, Islah al-Afrad is relevant as an alternative approach to addressing various social challenges, such as moral crises, social inequality, and the disintegration of values. This study contributes to reinforcing the perspective that social welfare in Islam is not merely material in nature, but also encompasses spiritual and moral dimensions as an integral whole.